Water-free process for eco-friendly purification of biodiesel obtained using a heterogeneous Ca-based catalyst - G. O. Ferrero (2014)
The technologies conventionally used for biodiesel purification imply high consumptions of both energy and water. In the present work, biodiesel was produced by transesterification using a very active calcium glyceroxide catalyst and purified using water-free processes. The study focused on soaps removal that was the main product impurity. The best results were obtained when the crude biodiesel (methyl ester content of 90.2-91.2 wt.% and calcium content of 372-393 ppm) was pretreated with Na2CO3 and afterward treated by an ion-exchange resin (6 wt.%) or a ceramic membrane (0.1 mu m).The purification was effective using biodiesel produced from both soybean oil and waste frying oil and the quality of the product agreed with the one obtained using the conventional water washing process. The effectiveness of the treatment could be explained by calcium elimination through precipitation as CaCO3 during pretreatment and sodium soaps removal by absorption into the resin or filtration by the ceramic membrane, according to the micelle formation mechanism. The studied process presents a high potential to remove calcium soaps from biodiesel.